The implications of Chinese strategic culture and counter-intervention upon Department of Defense space deterrence operations. Issue 5 (19th October 2016) - Stone, Christopher
ABSTRACT: The People's Republic of China (PRC) and its rapidly evolving space forces are viewed to be one of the principal threats to the United States' national security space infrastructure and the U.S. capability for timely force projection in the Pacific Theater. This view, especially since the 2007 kinetic anti-satellite (ASAT) weapons test, added emphasis to the Space Posture Review of 2010 and the Department of Defense's quest for deterrence as a means to secure the sanctuary of space from weaponization. This article will examine the strategic culture of the PRC and how it impacts the space deterrence philosophies of both the PRC and the U.S. Department of Defense.